2016
DOI: 10.17663/jwr.2016.18.3.301
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Seasonal Pollutant Distribution Characteristics of Contaminated Tributaries in Nakdong River Basin

Abstract: This study has performed comparative analysis on characteristics of contaminated 35 tributaries on seasonal variation/point discharge load/pollutant distribution of water quality factors(8) in order to understand the effect of the watershed in Nakdong River Basin. As a results, the water quality of BOD 5 (Biochemical Oxygen Demand), Chl-a(Chlorophyll a) and Fecal E. Coli shows Ⅱ grade at tributaries of more than 50% without COD(Chemical Oxygen Demand), TP(Total Phosphate), TOC(Total Oxygen Carbon) and TN(Total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Lee et al [9] also mentioned the impact of polluted tributaries on the Nakdong River mainstream for coliform bacteria. In addition, Yu et al [38] and Na et al [39] reported that highly contaminated secondary tributaries, which enter the Geumho River, could affect the water quality of the mid-and downstream section where Nongong station is located. Therefore, the rapid increase in the concentration of coliform bacteria at Nongong station was likely caused by pollutants carried by the Geumho River.…”
Section: Distribution Of Coliform Bacteriamentioning
confidence: 99%
“…Lee et al [9] also mentioned the impact of polluted tributaries on the Nakdong River mainstream for coliform bacteria. In addition, Yu et al [38] and Na et al [39] reported that highly contaminated secondary tributaries, which enter the Geumho River, could affect the water quality of the mid-and downstream section where Nongong station is located. Therefore, the rapid increase in the concentration of coliform bacteria at Nongong station was likely caused by pollutants carried by the Geumho River.…”
Section: Distribution Of Coliform Bacteriamentioning
confidence: 99%